Pelatihan Akuntansi dan Pemasaran Digital untuk UMKM Anggota Koperasi SAKTI di Kota Kediri - Widiawati, Hestin Sri; Linawati, Linawati; Nurdiwaty, Diah; Winarko, Sigit Puji; Faisol, Faisol; Zaman, Badrus (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
The activity aims to provide comprehensive accounting and digital marketing training to UMKM members of SAKTI Cooperation in Kediri City. UMKM plays an important role in the local economy, and these activities aim to enhance their financial and marketing capacity to support sustainable business growth. This dedication involves a series of interactive sessions that cover basic accounting concepts, balance sheets and loss reports, as well as digital marketing strategies including social media use, and online advertising. The 45 participants had an opportunity to share experiences, discuss, and identify joint solutions to challenges in their business. The result of this activity is an improvement in the understanding and skills of UMKM members of SAKTI Cooperation in managing their business finances more efficiently. In addition, the program also facilitates the growth of networking and collaboration among the UMKMs present, facilitating their understanding of the broader market potential, and supporting local economic development.